2013
DOI: 10.1371/journal.pone.0064080
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevalence by Race Co-Varies Closely with Concurrency and Number of Sex Partners in South Africa

Abstract: BackgroundHIV prevalence differs by more than an order of magnitude between South Africa's racial groups. Comparing the sexual behaviors and other risk factors for HIV transmission between the different races may shed light on the determinants of South Africa's generalized HIV epidemic.MethodsFive nationally representative and one city-representative population-based surveys of sexual behavior were used to assess the extent to which various risk factors co-varied with HIV prevalence by race in South Africa.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 32 publications
6
59
0
Order By: Relevance
“…Analysis of changes in risk behaviour in South Africa's ethnic groups, for example, suggests that ethnic groups most affected by HIV also showed a more rapid increase in condom usage, but this did not translate into lower HIV prevalence because there was little change in their rates of multiple and concurrent partnering, which remained considerably higher than among groups with a low prevalence of HIV. 24 Thirdly, the declines in syphilis prevalence may be due to some other unmeasured variable. The reasons behind the declines in syphilis prevalence are likely to be multifactorial and to vary somewhat among countries.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of changes in risk behaviour in South Africa's ethnic groups, for example, suggests that ethnic groups most affected by HIV also showed a more rapid increase in condom usage, but this did not translate into lower HIV prevalence because there was little change in their rates of multiple and concurrent partnering, which remained considerably higher than among groups with a low prevalence of HIV. 24 Thirdly, the declines in syphilis prevalence may be due to some other unmeasured variable. The reasons behind the declines in syphilis prevalence are likely to be multifactorial and to vary somewhat among countries.…”
Section: Discussionmentioning
confidence: 99%
“…Studying social contextual factors that influence individuals’ behaviors therefore requires multilevel approaches to begin to unpack these complex social processes. Like gender, race plays a role in HIV risk, and is a critical factor in South Africa’s HIV epidemic (Gilbert & Walker, 2002; Kenyon, Buyze, & Colebunders, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Other studies had samples of similar racial make-up to the current study. 100% of this study identified as black South African, consistent with other studies in South Africa on voluntary counseling and testing (Kilembe et al, 2015), IPV services (Adams et al, 2011) and general HIV prevalence (Kenyon, Buyze, & Colebunders, 2013). It is not surprising that a study serving Gauteng residents would include such high percentages of black South Africans given the province is 77.4% black South African (Statistics South Africa, 2012).…”
Section: Demographic Factorssupporting
confidence: 84%